Elaboración e implementación del curso virtual de la asignatura de historia y ciencias sociales para el primer año de bachillerato general unificado de informática para el colegio nacional “26 de Noviembre” de la ciudad de Zaruma, periodo 2013-2014 - Carrión Maldonado, Lauro Vinicio (2014)
School performance, the use of traditional pedagogy and a lack of technological resources in Education, is a widespread concern to parents and teachers, as the quality of education has always been a topic of discussion, so are a reliable alternative from an innovative technology perspective. For this reason the development of the next project "Development and implementation of the Virtual Course in History and Social Sciences subjects for first school year and it was carried out at " 26 de Noviembre " school of Zaruma city during the school year 2013-2014." is justifiable .The main goal at this proyect was to develop a constructivist approach and its implementation for the learning environment Moodle, which are inside the contents given by the Ministry of Education and Culture. The desire to implement this course, comes after previous research conducted using surveys, showing the needs and requirements that the institution has. Given this information and complying with the specific objectives, the validation tests required were conducted over the course surveys to teachers and students were applied, concluding that this tool provides a significant support in the learning process of the course History and Social Sciences.